Competitive swimming strokes applied by elite water-polo players - Mar'in, I. S.; Stepanova, O. N.; Karpov, V. Y.; Latushkina, E. N. (Theory and Practice of Physical Culture, 2017)
Subject to the study were the elite water-polo players` competitive swimming styles and their relative application rates versus the players` game roles in top-ranking competitions. Qualitative and quantitative input data for the study was provided by the content analysis of video replays of 43 matches at the 2016 Olympic Games in Rio de Janeiro with participation of the national teams of Greece, Japan, Australia, Brazil, Hungary, Croatia, Serbia, Montenegro, Italy, Spain, France and the USA. Subject to the content analysis were the competitive swimming style elements (units) and their application rates versus the players` game roles (defenders, utility forwards, wing forwards), the styles and their shares being rated in the relevant units - seconds, meters and game role ratios. The study data and analyses provided a set of reference points for the swimming practices modelling the elite players` competitive swimming styles. The study findings on the elite water-polo players` competitive swimming styles and their relative application rates may be applied for reference in the swimming training systems being designed for water-polo players of different skill levels.